Pengembangan Sistem Pencarian Pada Tujuh Kitab Hadis Menggunakan Algoritma Knuth-Morris-Pratt - Desy Kartika Sari; Dwi Sakethi; Rizky Prabowo (Jurnal Komputasi, 2019)
Hadith search information system requires the main function that is the word search method to make it easier for users to find the word they are looking for. Word search can be conducted by using string matching algorithm to obtain the search term, one of them is Knuth-Morris-Pratt algorithm. This algorithm has two stages in the search process, namely the pre-KMP process which is the stage of giving a shift value in the keyword (pattern) and KMP-Search stage which is a matching phase between text and keyword (pattern). The process of matching text and patterns is conducted from the left to the right based on the value of the shift that has been obtained in the pre-KMP process. The search time is influenced by the length of the text on the database and the pattern the user is looking for, the longer the text and pattern, the search time will increase.